Cancer chemotherapy drug wastage in a tertiary care hospital in India—A 3‐month prospective and 1‐year retrospective study. Issue 10 (1st August 2019) - Gopisankar, MG; Wahlang, Julie; Jagtap, Vikas; Sarkar, Chayna; Purnima Devi, L; Harris, Caleb
Abstract : This study prospectively quantified wastage of cancer chemotherapeutic drugs in an oncology unit to find the associated cost in 3 months. Retrospective analysis of drug usage for 12 months was also conducted to determine the expected drug loss in 1 year. The effect of vial sharing was evaluated under the assumption of sharing. A significant drug wastage of 19.72% (95% confidence interval [CI], 14.52–24.93%) in 3 months and 17.14% (95% CI 14.69–19.59%) in 1 year occurred in our oncology unit. Number of vials purchased ( r  = 0.362, p  < 0.01), weight ( r  = −0.146, P  < .01) and body surface area ( r  = −0.26, P  < .01) correlated with the drug wasted. Vial sharing assumption showed a 9% (95% CI, 2.5–15.5%) reduction in cost in 1 year.